Permeable barriers: a conversation about poetry. Issue 3 (3rd July 2021) - Webb, Jen; Coles, Katharine
ABSTRACT: A great many successful poets earn their living as members of the university community. While teaching, research and administration can provide a reasonable and a reliable income, it has an impact not only on how much time is available for writing, but also what sorts of thinking emerge; on the ways in which relationships and responsibilities intertwine, and how to find ways to balance competing priorities. In this conversation between two poet academics, Jen and Katharine talk through their own experiences, grounded in scholarly thinking, and particularly address the role of language, meaning and materiality in the charting and the crafting of a life.